Molecular characteristics and outcomes in Hispanic and non‐Hispanic patients with acute myeloid leukemia. Issue 4 (18th October 2022) - Bradley, Terrence; Kwon, Deukwoo; Monge, Jorge; Sekeres, Mikkael; Chandhok, Namrata; Thomassen, Amber; Swords, Ronan; Padron, Eric; Lancet, Jeff; Talati, Chetasi; Watts, Justin
Abstract: Hispanic patients have been reported to have an increased incidence of AML and possibly inferior outcomes compared to non‐Hispanics. We conducted a retrospective study of 225 AML patients (58 Hispanic and 167 non‐Hispanic) at two academic medical centers in Florida. Disease characteristics, cytogenetics, mutation profiles, and clinical outcomes were assessed. Hispanic patients were younger at presentation than non‐Hispanics ( p = 0.0013). We found associations between single gene mutations and ethnicity, with IDH1 mutations being more common in non‐Hispanics (95.2% vs. 4.8%, p = 0.0182) and WT1 mutations more common in Hispanics (62.5% vs. 37.5%, p = 0.0455). We also found an emerging trend towards adverse risk cytogenetics in Hispanic patients ( p = 0.1796), as well as high risk fusions such as MLL‐r (70% vs. 30%, p = 0.004). There was no difference in overall survival (OS) between Hispanic and non‐Hispanics patients. When examining only newly diagnosed patients ( n = 105), there was improved OS in Hispanics (median 44.7 months vs. 14 months, p = 0.026) by univariate analysis and equivalent OS by multivariate analysis (hazard ratio = 1.52 [95% CI = 0.74–3.15]). Hispanics with a driver mutation not class‐defining had improved survival compared to non‐Hispanics. Our study demonstrates significant genetic differences between Floridian Hispanics and non‐Hispanics, but no difference in OS in patients treated at an academic medical center.